Politik Tindak Pidana Penerbangan: Tinjauan Pelanggaran Kedaulatan Negara di Ruang Udara Indonesia - Sulastri, Lusia (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2021)
This research is intended to examine the regulation of punishment and prosecution for violations of state sovereignty in Indonesian airspace. The legal vacuum of clear regulation regarding the sovereignty of air space that is firm becomes the urgency of punishment for violations of state sovereignty in Indonesia’s air space. Indonesia has Law Number 1 of 2009 concerning Aviation where Article 414 states that anyone who operates a foreign aircraft in the territory of the Unitary State of the Republic of Indonesia without a permit shall be punished with imprisonment for a maximum of 5 (five) years or a fine of a maximum of Rp. 2,000,000. .000,00 (two billion rupiah). However, this arrangement has not been effective in ensnaring people who violate state sovereignty in Indonesian airspace so violations of State Sovereignty in Indonesian Airspace have increased. Air violations that often occur in the territory of the Republic of Indonesia suggest weaknesses in law enforcement.